Ultrasound-guided trans-rectal high-intensity focused ultrasound (HIFU) for advanced cervical cancer ablation is feasible: a case report. Issue 1 (December 2015) - Abel, M.; Ahmed, H.; Leen, E.; Park, E.; Chen, M.; Wasan, H.; Price, P.; Monzon, L.; Gedroyc, W.; Abel, P.
Abstract Introduction High-intensity focused ultrasound (HIFU) is an ablative treatment undergoing assessment for the treatment of benign and malignant disease. We describe the first reported intracavitary HIFU ablation for recurrent, unresectable and symptomatic cervical cancer. Case description A 38 year old woman receiving palliative chemotherapy for metastatic cervical adenocarcinoma was offered ablative treatment from an intracavitary trans-rectal HIFU device (Sonablate® 500). Pre-treatment symptoms included vaginal bleeding and discharge that were sufficient to impede her quality of life. No peri-procedural adverse events occurred. Symptoms resolved completely immediately post-procedure, reappeared at 7 days, increasing to pre-procedural levels by day 30. Discussion and evaluation This first time experience of intracavitary cervical HIFU suggests that it is feasible for palliation of advanced cervical cancer, with no early evidence of unexpected toxicity. Ethical approval had also been granted for the use of per-vaginal access if appropriate. This route, alone or in combination with the rectal route, may provide increased accessibility in future patients with a redesigned device more suited to trans-vaginal ablations. Conclusion Intracavitary HIFU is a potentially safe procedure for the treatment of cervical cancer and able to provide symptomatic improvement in the palliative setting.